Homeownership, unemployment and commuting distances - Yuval Kantor; Peter Nijkamp; Jan Rouwendal (European Regional Science Association (ERSA), 2010)
According to Oswald's hypothesis homeowners experience more problems in finding a new job after becoming unemployed because their moving costs are higher than those of renters. Empirical research has revealed that this effect is counteracted by the job search behavior of unemployed homeowners: they accept a job on the local labor market, that is, a job that does not force them to move to a different residential location, more frequently than unemployed renters. One possible explanation of this result is that the local labor market is larger for homeowners than for renters, in the sense that they are willing to accept longer commutes. This suggests that the longer commutes of homeowners (a well known empirical fact) are partly caused by higher moving costs. In this paper we analyze the validity of this explanation by investigating the relationship between homeownership and commutes while controlling for other variables, and possible effects of selection and heterogeneity.
Keywords: 330